Evaluasi Kepuasan Pengguna M-Payment sebagai Alat Pembayaran Online di Indonesia - Rahma Rina Wijayanti; Oryza Ardiarisca; Rediyanto Putra (Journal of Applied Accounting and Taxation, 2021)
Mobile Payment (M-Payment) is currently widely used in Indonesia to make payment transactions online. This is because the number of internet users in Indonesia is getting bigger. This article aims to test the level of satisfaction of users of m-payment applications in Indonesia. This study uses primary data in the form of a questionnaire distributed to respondents. The selection of respondents was carried out using the method accidental sampling. Analysis of the research data was carried out using the Fishbein, IPA, and CSI methods. The attributes used to measure the level of satisfaction of m-payment users are attractiveness, ease of use, efficiency, security, stimulation, usefulness. The results of this study indicate that the m-payment application users are very satisfied with the performance of the m-payment application used. The results also show that there are 2 (two) attributes that have good performance in the view of m-payment application users, namely efficiency and ease of use which, according to user ratings, have performance that exceeds user expectations. The users consider that the usefulness of m-payment application used still has a performance below expectations. Thus, the provider of the m-payment application is supposed to improve the quality of the existing m-payment application.